Parathyroid Hormone Measurement in Chronic Kidney Disease: From Basics to Clinical Implications - Kittrawee Kritmetapak; Chatlert Pongchaiyakul (International Journal of Nephrology)
Accurate measurement of parathyroid hormone (PTH) is crucial for therapeutic decision-making in patients with chronic kidney disease-mineral and bone disorder (CKD-MBD). The second-generation PTH assays, often referred to as “intact PTH” assays, are the current standard and most available assays in clinical practice. However, intact PTH assays measure both full-length biologically active PTH and heterogeneous PTH fragments in the circulation, providing the equivocal value of PTH measurement in patients with CKD-MBD. Due to the variability of PTH assays, preanalytical sample errors, and the phenomenon of end-organ PTH hyporesponsiveness, current CKD-MBD guidelines recommend a wide range for serum PTH targets (2–9 the upper normal limit of the intact PTH assay) in dialysis patients to diminish the risk of developing adynamic bone disease. Nevertheless, a sizeable proportion of CKD patients still experience renal osteodystrophy despite having serum PTH levels within the recommended range. The primary cause of this inconsistency is the analytical interference of various PTH fragments and oxidized PTH forms that considerably accumulate in CKD patients. Therefore, a new mass spectrometry-based assay, which is capable of specifically measuring the whole spectra of PTH fragments, can potentially improve diagnostic accuracy for renal osteodystrophy. However, the effects of different PTH fragments on bone metabolism, vascular calcification, and mortality in CKD patients warrant further research.